2020
DOI: 10.1101/2020.06.22.165290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human brain function during pattern separation follows hippocampal and neocortical connectivity gradients

Abstract: Episodic memory is our ability to remember past events accurately. Pattern separation, the process of of orthogonalizing similar aspects of external information into nonoverlapping representations, is one of its mechanisms. Converging evidence suggests a pivotal role of the hippocampus, in concert with neocortical areas, in this process. The current study aimed to identify principal dimensions of functional activation associated with pattern separation in hippocampal and neocortical areas, in both healthy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 100 publications
(119 reference statements)
0
10
0
Order By: Relevance
“…Murphy et al, 2019). In the study of brain diseases associated with macroscale dysfunction, connectivity gradients have furthermore been used to contextualize changes in brain network architecture (Larivière et al, 2020; Li et al, 2020), supporting their utility to serve as coordinate systems of macroscale functional interactions in healthy and diseased brains.…”
Section: Discussionmentioning
confidence: 99%
“…Murphy et al, 2019). In the study of brain diseases associated with macroscale dysfunction, connectivity gradients have furthermore been used to contextualize changes in brain network architecture (Larivière et al, 2020; Li et al, 2020), supporting their utility to serve as coordinate systems of macroscale functional interactions in healthy and diseased brains.…”
Section: Discussionmentioning
confidence: 99%
“…Across scales, we assessed correlations of task effects with cognitive performance in all participants 22, 43 using permutation-based analyses, each entailing 10000 permutations. Voxel-based regressions were conducted with SnPM13; age, sex and group were nuisance covariates.…”
Section: Methodsmentioning
confidence: 99%
“…As such, it recapitulates established models of cortical hierarchy, 39 and offers a formal framework to characterize organizational aspects of cognitive activity, as exemplified by recent work in healthy adults 4042 and people with TLE engaged in a pattern separation task. 43 By conveying regional, systems-level and global viewpoints on the neural signatures of cognitive dysfunction in epilepsy, our innovative approach proves sensitive to both localized and higher-order abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Gradient techniques allow a continuous description of the functional connectome compared to discrete network representations of the brain [32][33][34] . Using these gradients, prior studies have found relationships of hippocampal functional connectivity with anatomical organization and microstructure 31 , as well as performance on memory recollection 30 , and pattern separation tasks 29 . It is possible such individual variations in function are due to genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…A second axis referred to as the transverse or medio-lateral axis emphasizes connectome differences in medial and lateral hippocampal portions 18,24,29,30 . In recent years, several groups have used dimension reduction techniques, commonly known as gradients, to provide a parsimonious account of hippocampal functional connectivity [31][32][33] . Gradient techniques allow a continuous description of the functional connectome compared to discrete network representations of the brain [34][35][36] .…”
Section: Introductionmentioning
confidence: 99%